Stem solidness as an important factor for wheat protection from European wheat stem sawfly (Cephus pygmaeus L.) in Altai - S. B. Lepekhov; V. A. Petin; M. V. Chebatareva (Труды по прикладной ботанике, генетике и селекции)
Background. European wheat stem sawfly (Cephus pygmaeus L.) is the main pest of wheat in Altai Territory, Russia. Resistance of host plants to this insect is based on a solid stem. The effect of a solid stem on the infestation of wheat stem sawfly larvae and on agronomic traits of spring bread wheat under the conditions of Altai Territory has not been studied.Materials and methods. The study was conducted on the experimental field of the Federal Altai Scientific Centre of Agro-BioTechnologies, Barnaul, Russia, in 2019–2021. The index of stem solidness was assessed according to a 20 point scale. The interplay between stem solidness and wheat stem sawfly larvae infestation of wheat plants was studied on 12 genotypes. The effect of stem solidness on agronomic traits was studied on 6 pairs of sister lines. One hundred cultivars were studied for the stem solidness index and 184 cultivars were tested for their resistance to wheat stem sawfly.Results. Stem solidness negatively correlated with wheat stem sawfly infestation (Spearman’s rank correlation coefficient was rs  = –0.77 in 2019 and rs  = –0.80 in 2020). Sister lines with a solid stem had significantly shorter plant height (–5 cm), less kernels per spikelet (–0.11 kernels), 1000 grain weight (–1.7 g) and grain weight per spike (–0.08 g), but higher grain weight per tiller spike (+0.11 g), compared to sister lines with a hollow stem averaged over two years. Stem solidness had no negative effect on yield or grain quality. Eleven cultivars with a solid stem index higher than 15 points were identified (‘Ershovskaya 33’, ‘Izera’, ‘Kvintus’, ‘KWS Akvilon’, ‘Tybalt’, ‘Cunningham’, ‘KW 240-3-13’, ‘KWS 3.13’, ‘Lillian’, ‘Sparrow’, ‘WW-4’).Conclusion. Stem solidness significantly decreases the damage from wheat stem sawfly and has no negative effect on yield or gluten and protein content in grain. The abovementioned cultivars with a solid stem are recommended for use in breeding for resistance to wheat stem sawfly.